Child compound Endothelium corneum attenuates gastrointestinal dysmotility through regulating the homeostasis of brain-gut-microbiota axis in functional dyspepsia rats. (10th August 2019) - He, Yixin; Yang, Chun; Wang, Ping; Yang, Liu; Wu, Hui; Liu, Hongmin; Qi, Muge; Guo, Zhonghua; Li, Jianghua; Shi, Hailian; Wu, Xiaojun; Hu, Zhibi
Abstract: Ethnopharmacological relevance: Nowadays, there is no specific effective western medicine for functional dyspepsia (FD), especially in children. Clinically, child compound Endothelium corneum (CCEC) has shown to be effective for the therapy of FD, however, the underlying mechanism has not been elucidated yet. Materials and methods: FD was induced in rats by irregular diet plus dilute hydrochloric acid feeding. Gastric emptying and small intestinal transit were examined by intragastric gavage with Evans blue. Histopathology was assessed by H&E staining. Gastrointestinal hormones and brain gut peptides were measured by ELISA assay. mRNA expression level was quantified by real-time PCR. Protein expression level was detected by western blotting assay. Gut microbiota was analyzed by 16S rRNA miseq sequencing. Results: CCEC significantly enhanced gastric emptying and small intestinal transit of FD rats, and prominently suppressed gastrointestinal microinflammation. At phylum level, CCEC prevented the decrease of Firmicutes and the increase of Bacteroidetes in gut of FD rats. In stomach of FD rats, MTL, CCK and VIP levels were significantly increased, which could be repressed by CCEC; however, the decreased GAS level could not be elevated by CCEC. In small intestine of FD rats, MTL and GAS levels were decreased, while VIP content was increased. These alterations could be effectively reversed by CCEC. NPY levels in serum, small intestine and hypothalamus of FD rats were significantly decreased, which could be rescued by CCEC. Moreover, the over-activated POMC/Stat3/Akt pathway in hypothalamus of FD rats could be suppressed by CCEC. Conclusion: CCEC enhanced gastrointestinal motility probably through rebalancing the homeostasis of brain-gut-microbiota axis in FD rats. The novel findings may provide insightful theoretical basis for its clinical employment. Graphical abstract: Image 1